Effect of light and dark treatments on photosynthetic key enzymes in rice - JIANG De-an; WENG Xiao-yan; LU Qing; ZHEN Bing-song (浙江大学学报. 农业与生命科学版, 2001)
After 24 h darkness treatments, Rubisco contents and ratio of Rubisco to soluble protein in the rice seedling increased with illumination rising. When the seedling was put in darkness after 2 h illumination, Rubisco contents decreased at first 20 min, which suggested that Rubisco highly turnovers under alternative conditions of light and dark. Initial Rubisco carboxylation activity increased rapidly and the rate was faster than that of Rubisco content. The more intensive light, the shorter time maximum activity of the enzyme required. After 2 h illumination, initial and total activities of Rubisco declined so fast that the activities decreased four tims in 1 h. Rubisco activase content rose gradually after illumination and declined slowly in darkness, but it continuously lowered during 45 h-darkness. Rubisco activase activation required low intensity. After 2 h illumination, Rubisco activase activity decreased sharply in dark.